Action research: Enhancing Classroom Practice and Fulfilling Learning Responsibilities with Guided Note Taking (GNT) and Teams Games Tournament (TGT) Models - Puspasari, Emma Yunika (Unversitas Negeri Malang, 2017)
Abstract The purpose of this research is to explain how the application of learning methods Guided Note Taking (GNT) and learning model Teams Games Tournament (TGT) in the subjects of economics and whether the application of learning methods Guided Note Taking (GNT) and learning model Teams Games Tournament (TGT) on economic subjects can improve student learning outcomes. This research used a qualitative approach to the type of Classroom Action Research (CAR) so that the presence and role of researchers in the field is indispensable. Data studied were focused on student learning outcomes. The results from 1th cycles shows by percentage the thoroughness of learning outcomes is the pre test in the value of 0% and a post-test at 22,85%. In the second cycle of learning outcomes obtained by the percentage of completeness study results showed an increase in value of 22,85% pre test and post test amounted to 77,14%. And the affective domain also increased from initially that no students were classified in the very good category, become 3 students that are classified as very good. And the psychomotor domain also increased from 17 students is in good category become 27 students is in good category. Keywords: Action Research, Guided Note Taking (GNT), Teams Games Tournament (TMT) DOI: 10.17977/um013v1i12017p036